2019
DOI: 10.1038/s41467-019-13202-5
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-catalysed sequential singlet fission

Abstract: Singlet fission is the photoinduced conversion of a singlet exciton into two triplet states of half-energy. This multiplication mechanism has been successfully applied to improve the efficiency of single-junction solar cells in the visible spectral range. Here we show that singlet fission may also occur via a sequential mechanism, where the two triplet states are generated consecutively by exploiting oxygen as a catalyst. This sequential formation of carriers is demonstrated for two acene-like molecules in sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 31 publications
1
26
1
Order By: Relevance
“…As the TA experiments conducted here were undertaken under standard atmospheric conditions, it is also possible that dissolved oxygen may contribute to exciton quenching at the NP surface. However, previous studies of acene quenching by triplet oxygen have measured rate coefficients on the order of 10 9 to 10 10 s –1 , which is 1–2 orders of magnitude lower than the picosecond-scale S 1 deactivation observed here. , Therefore, singlet quenching by triplet oxygen is also unlikely to be the main cause of the non-radiative singlet decay observed here. Picosecond-scale non-radiative singlet decay in aqueously dispersed fullerene NPs has previously been attributed to exciton quenching by water .…”
Section: Resultscontrasting
confidence: 72%
“…As the TA experiments conducted here were undertaken under standard atmospheric conditions, it is also possible that dissolved oxygen may contribute to exciton quenching at the NP surface. However, previous studies of acene quenching by triplet oxygen have measured rate coefficients on the order of 10 9 to 10 10 s –1 , which is 1–2 orders of magnitude lower than the picosecond-scale S 1 deactivation observed here. , Therefore, singlet quenching by triplet oxygen is also unlikely to be the main cause of the non-radiative singlet decay observed here. Picosecond-scale non-radiative singlet decay in aqueously dispersed fullerene NPs has previously been attributed to exciton quenching by water .…”
Section: Resultscontrasting
confidence: 72%
“…However, previous studies of acene quenching by triplet oxygen have measured rate coefficients on the order of 10 9 -10 10 s −1 , which is 1-2 orders of magnitude lower than the picosecond-scale S 1 deactivation observed here. 49,50 Therefore, singlet quenching by triplet oxygen is also unlikely to be the main cause of the non-radiative singlet decay observed here. Picosecond-scale non-radiative singlet decay in aqueously-dispersed fullerene NPs has previously been attributed to exciton quenching by water.…”
Section: Singlet Exciton Quenchingmentioning
confidence: 75%
“…As the resulting estimation 80.7 × 10 6 s –1 is significantly lower than the observed values in all four molecules, this reaction channel is ruled out. The further possibility of a direct, diffusion-controlled SF process can be excluded due to the low concentration of the samples (≪0.1 mmol L –1 ). ,, Thus, it is concluded that the triplet state is formed via an ISC process with the rate constant k 2 . This is supported by the systematically increasing rates with substituent size for the three halogenated TAPPs and the concomitant decrease of the fluorescence quantum yield .…”
Section: Discussionmentioning
confidence: 99%
“…The formation of a triplet state in solution can in principle occur via ISC or, due to the high S 1 –T 1 energy gap (Table ), energy transfer to 3 O 2 . For the latter, an upper limit can be calculated using the quenching rate of oxygen and its concentration in acetonitrile .…”
Section: Discussionmentioning
confidence: 99%